2007
DOI: 10.1007/s00216-007-1749-2
|View full text |Cite
|
Sign up to set email alerts
|

The study of surface properties of an IgE-sensitive aptasensor using an acoustic method

Abstract: We applied the acoustic transverse shear mode (TSM) method for study of the surface properties of a DNA aptasensor that specifically binds human immunoglobulin E (IgE). The biotinylated 45-mer DNA aptamers were immobilized on the surface of a self-assembled layer composed of a mixture of polyamidoamine dendrimers of the fourth generation with 1-hexadecanetiol covered by neutravidin. Using the TSM method, we studied the kinetics of changes of the series resonant frequency, f(s), and the motional resistance, R(m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…Gokulrangen et al have reported an aptamer-based bioanalysis for IgE detection using fluorescence anisotropy [54], and obtained a limit of detection of 350 pM. Moreover, Snejdarkove et al have studied surface properties of an IgE-sensitive aptasenosr using an acoustic method [55]. In our study, we detected IgE in the range of 250 pM -160 nM using aptamer-based CNTFETs, indicating that CNTFETs are useful for detecting proteins such as IgE.…”
Section: Aptamer-based Carbon Nanotube Immunosensorsmentioning
confidence: 49%
“…Gokulrangen et al have reported an aptamer-based bioanalysis for IgE detection using fluorescence anisotropy [54], and obtained a limit of detection of 350 pM. Moreover, Snejdarkove et al have studied surface properties of an IgE-sensitive aptasenosr using an acoustic method [55]. In our study, we detected IgE in the range of 250 pM -160 nM using aptamer-based CNTFETs, indicating that CNTFETs are useful for detecting proteins such as IgE.…”
Section: Aptamer-based Carbon Nanotube Immunosensorsmentioning
confidence: 49%
“…QCM method allowing also the determination of the number of IgE bounded to the surface. However, as we have shown in our recent paper [19], the changes of the frequency due to the binding of IgE to DNA aptamers immobilized at the surface of quartz crystal are only partially connected with the changes of the mass. For correct detection of the surface concentration of IgE it is necessary to take into consideration also the viscous forces, that may be determined by measuring so called motional resistance, R m .…”
Section: Electrochemical Aptasensors Based On Aptamers Conjugated Witmentioning
confidence: 85%
“…Using glutaraldehyde, crosslinking of avidin to a dendrimer surface is possible, so it can be then used for immobilization of biotinylated aptamers. The advantage of dendrimers is their high stability and relatively large surface in comparison with flat electrode [57,61]. So et al [16] reported immobilization of thrombin aptamer onto the surface of carbon nanotubes.…”
Section: Immobilization Of Aptamers On Solid Supportsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of these parameters reflect the conditions at the interface with respect to mass and interfacial properties [21]. A network analyzer (8712ES Network/Spectrum analyzer, Agilent Technology, USA) was used to determine f S and R m values (see [22] for more details). All experiments were performed at temperature 20 AE 1 8C.…”
Section: Determination Of Interaction Of the Antibodies Withmentioning
confidence: 99%